PEMANFAATAN CAMPURAN FLY ASH DAN LDPE SEBAGAI SUBTITUSI AGREGAT HALUS PADA PAVING BLOCK - Putri Rahmadini Utami (Teknik Sipil, Fakultas Teknik Universitas Negeri Jakarta, 2023)
Paving blocks are product building cement, aggregate and water used as ground pavement. This study aims to determine the characteristics of paving blocks by utilizing Fly Ash and LDPE as partial sand substitution so that it can be seen their effect on quality requirements referring to SNI 03-0691-1996. This study uses experiment method with paving block specimens measuring 210 mm x 105 mm x 60 mm in form of beam. Utilization Fly Ash and LDPE as partial substitution of fine aggregate with various percentages of 0%, 5%, 7.5%, 10%, 12.5% and 15%. Tests on the specimens were carried out at of 28 days in accordance SNI 03-0691-1996 regarding paving blocks, in the form of compressive strength tests, wear resistance tests and water absorption tests. The results of this study indicate that the effect of using Fly Ash and LDPE on paving blocks can improve its quality with the right proportions. The optimum compressive strength is found in variations of 0% and 7.5%, respectively, of 17.2 MPa and 20 MPa.. Variations of 5%, 7.5%, 10%, and 12.5% fall into grade A for wear resistance testing. In the water absorption test, the variation of 7.5% and 12.5% is classified as B quality.